1975
DOI: 10.1161/01.res.37.6.787
|View full text |Cite
|
Sign up to set email alerts
|

Muscle stiffness determined from canine left ventricular pressure-volume curves.

Abstract: We measured pressure-volume curves in nine excised dog ventricles and stress-strain curves in two to five muscle specimens from each ventricle to verify a derived formula that relates muscle stiffness to the ventricular pressure-volume curve. The assumptions underlying this formula are: (1) the ventricle is a uniform spherical shell, (2) all muscle fibers carry average stress and deform as if they were at the midwall, (3) static equilibrium exists, (4) internal pressure induces the only load, and (5) the muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 14 publications
1
31
0
1
Order By: Relevance
“…LV stiffness is governed by a complex interplay of myocardial stiffness (largely related to the tissue collagen content), 23 ventricular geometry (hypertrophy 24 and distension 25 ), and myocardial relaxation. 26 Our findings that K LV in hypertensive patients is related to CVF but not to the degree of LV hypertrophy and relaxation abnormalities and that LV volumes were not increased in these patients (data not shown) strongly suggest that myocardial fibrosis is the main determinant of LV stiffness in essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…LV stiffness is governed by a complex interplay of myocardial stiffness (largely related to the tissue collagen content), 23 ventricular geometry (hypertrophy 24 and distension 25 ), and myocardial relaxation. 26 Our findings that K LV in hypertensive patients is related to CVF but not to the degree of LV hypertrophy and relaxation abnormalities and that LV volumes were not increased in these patients (data not shown) strongly suggest that myocardial fibrosis is the main determinant of LV stiffness in essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that with high sensitivity tracings, measurements of muscle length at the point where resting stress first rises above zero are reproducible, i.e., ±8%. Furthermore, Glantz and Kernoff (11) have shown that d is relatively insensitive to small changes in initial muscle length.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed passive stiffness from the stress-strain relationship calculating the elastic constants a and ,8 as described by Glantz and Kernoff (11). Because the stress-strain relationship of cardiac muscle is monoexponential over the physiologic range of stress (11,12), the elastic constants can be derived from: a = a (e#' -1) where a = force/instantaneous cross sectional area and e (Lagrangian strain) = 1 -10/10, 1 being unstressed muscle length. We also calculated the tangent modulus or elastic stiffness (da/ de) from do/de = ,a + #a (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glantz and Kernoff 17 showed such computations were possible given enough data, but even their theory failed when confronted with the limited amount of information possible in a clinical setting. …”
Section: Table 1 Correlations Between Ventricular Stiffness Parametermentioning
confidence: 99%